Historical development of clinical reasoning - Jorge Luis Losada Guerra; Elena V. Hernández Navarro; Miguel Salvat Quesada (Centro Provincial de Información de Ciencias Médicas, 2019)
Clinical reasoning as cognitive process regulator of medical diagnosis has experienced considerable changes through the history. This work is intended to carried out a historical description of clinical reasoning, to contribute in the reinforcement of its relevance as rational component of the clinical method, responsible to a great extent, of the medical diagnosis efficiency. The study covered the transformations of the clinical reasoning from the Ancient times to the Contemporary Age, taking into account the main effective philosophical tendencies existing in each period.  It was concluded that the description of the stream of consciousness related to the reasoning through the historical and philosophical development of humanity favors to keep the postulates of the clinical reasoning in line with the medical practice and the teaching-learning process of the clinical subjects in the contemporary conceptions.